Implementation of Digital Finance for SME: Case Study of Digital-Based Business Incubator Program and Adoption Challenges in Palu City, Indonesia - Dasi, Wilasini Dewi; Husnah, H.; Nofal, Mohammad; Samudra, Suryadi (Golden Ratio of Finance Management, 2025)
The era of digitalization has brought changes in various economic sectors, including Micro, Small, and Medium Enterprises (SMEs) in Indonesia. This research discusses the implementation of digital finance in SMEs assisted by the Digital-Based Business Incubator of Palu City. The main focus is how the business incubator's coaching program and SME's level of digital literacy affect the adoption of digital financial technology. This study aims to analyze the implementation of digital finance in Business Incubator SMEs through a quantitative approach, data obtained from distributing questionnaires to SMEs involved in the incubation program. Multiple linear analysis methods with SPSS statistical tools were used to achieve the research objectives. The research was conducted on SMEs registered in the Business Incubator, totaling 52 SMEs, with a research sample of 40 SMEs. The results showed that the Business Incubator coaching program and digital literacy significantly positively affected the implementation of digital finance in SMEs. Targeted coaching programs and adequate digital literacy are proven to increase SME adoption of digital financial technology.